2022
DOI: 10.1111/hsc.13844
|View full text |Cite
|
Sign up to set email alerts
|

Collectively learning to talk about personal concerns in a peer‐led youth program: A field study of a community of practice

Abstract: Youth peer‐support is an increasingly established approach to youth work. Drawing on Wenger's theory of a ‘community of practice’, this study explored social learning processes in an Australian community‐based and peer‐led youth program for young people from disadvantaged backgrounds. Social learning was conceptualised as arising from processes of ‘negotiated meaning’, which Wenger described as a duality of ‘participation’ and ‘reification’. The study was designed as a qualitative field study drawing on partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…23 25 28 30 A summary of the features, writing approach, and examples of published articles for each type of qualitative and quantitative research is shown in Table 1 . 31 32 33 34 35 36 37 38 39 40 41 42 43 …”
Section: Types Of Researchmentioning
confidence: 99%
“…23 25 28 30 A summary of the features, writing approach, and examples of published articles for each type of qualitative and quantitative research is shown in Table 1 . 31 32 33 34 35 36 37 38 39 40 41 42 43 …”
Section: Types Of Researchmentioning
confidence: 99%
“…There has been a proliferation of CoPs within healthcare, education, and other professional domains, including the emerging use of virtual technologies to support CoPs [ 18 ]. Other relevant, emerging areas including youth-led CoPs [ 19 ], and CoPs within the area of Indigenous health and wellbeing, as well as CoPs that advance community-based participation and interests. Wexler and colleagues, for example, describe building a CoP with Indigenous leaders and service providers in a rural Alaska [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from all studies were subjected to thematic analysis. Methods and results have been reported elsewhere [26,[31][32][33]. The approaches outlined below may assist services as they develop their response to the special commission and also have broad applicability, beyond the NSW health system.…”
mentioning
confidence: 99%